A Facile One-step Electrochemical Synthesis of Nickel Nanoparticle/Graphene Composites for Non-enzymatic Biosensor Applications. (2015) - Darvishi, S.; Karmizadeh, F.; Kharaziha, M.
Abstract: In recent years, graphene, two-dimensional closely packed honey-comb carbon lattice, has been attracting much attention in the field of electrochemistry due to its intrinsic properties and merits. Moreover, nickel has found extensive use in preparation of biosensors. In the present study, we applied a simple and straightforward approach for the development of nickel nanoparticle-graphene sheet (NiNP-GS) modified glassy carbon electrode (GCE) for nonenzymatic biosensor applications. The nanocomposites of NiNP-GS with various concentrations of nickel nanoparticles (NiNPs) synthesized through in situ chemical reduction procedure. In order to develop NiNP-GS modified GCE, 10 μl suspension of NiNP-GS dispersed in deionized water was dripped on GCE surface and dried for 24 h at room temperature. The nanocomposites have been characterized using scanning electron microscope (SEM) and X-ray diffraction (XRD). Additionally, the sensing performance was evaluated by cyclic voltammetry. Results clearly demonstrated that the as-synthesized NiNPs with diameters less than 100 nm were well uniformly distributed on the surface of graphene nanosheets on graphene sheets. The characterization data also demonstrated that the nanocomposite film had a large surface area and enhanced electron-transfer rate compared with only Ni nanoparticles, due to an efficient electrical network through NiNPs direct anchoring on the surface of graphene. Furthermore, the sensivity and reproducibility of prepared electrode were better than other nickel electrodes reported. The good analytical performance, low cost and simple fabrication procedure make this novel electrode material promising for the development of effective non-enzymatic glucose sensor.